Neurological Manifestations of Coronavirus Disease 2019: A Comprehensive Review and Meta-Analysis of the First 6 Months of Pandemic Reporting - Huth, Samuel F.; Cho, Sung-Min; Robba, Chiara; Highton, David; Battaglini, Denise; Bellapart, Judith; Suen, Jacky Y.; Li Bassi, Gianluigi; Taccone, Fabio Silvio; Arora, Rakesh C.; Whitman, Glenn; Fraser, John F.; et al. (Frontiers in Neurology, 2021)
Background: There is growing evidence that SARS-Cov-2 infection is associated with severe neurological complications. Understanding the nature and prevalence of these neurologic manifestations is essential for identifying higher-risk patients and projecting demand for ongoing resource utilisation. This review and meta-analysis report the neurologic manifestations identified in hospitalised COVID-19 patients and provide a preliminary estimate of disease prevalence. Methods: MEDLINE, Embase and Scopus were searched for studies reporting the occurrence of neurological complications in hospitalised COVID-19 patients. Results: A total of 2,207 unique entries were identified and screened, among which 14 cohort studies and 53 case reports were included, reporting on a total of 8,577 patients. Central nervous system manifestations included ischemic stroke (n = 226), delirium (n = 79), intracranial haemorrhage (ICH, n = 57), meningoencephalitis (n = 13), seizures (n = 3), and acute demyelinating encephalitis (n = 2). Peripheral nervous system manifestations included Guillain-Barrè Syndrome (n = 21) and other peripheral neuropathies (n = 3). The pooled period prevalence of ischemic stroke from identified studies was 1.3% [95%CI: 0.9–1.8%, 102/7,715] in all hospitalised COVID-19 patients, and 2.8% [95%CI: 1.0–4.6%, 9/318] among COVID-19 patients admitted to ICU. The pooled prevalence of ICH was estimated at 0.4% [95%CI: 0–0.8%, 6/1,006]. Conclusions: The COVID-19 pandemic exerts a substantial neurologic burden which may have residual effects on patients and healthcare systems for years. Low quality evidence impedes the ability to accurately predict the magnitude of this burden. Robust studies with standardised screening and case definitions are required to improve understanding of this disease and optimise treatment of individuals at higher risk for neurologic sequelae.